The optimization technique for a hybrid renewable energy system based on solar-hydrogen generation - Shklyarskiy, Yaroslav; Skvortsov, Ivan; Sutikno, Tole; Manap, Mustafa (Institute of Advanced Engineering and Science, 2024)
This paper provides an in-depth analysis of the challenges associated with the commonly used optimization methods for determining the configuration of hybrid renewable energy systems that rely on solar generation and hydrogen technologies. It highlights the key research directions in this field and includes a brief overview of the number of publications related to the subject. The standard topology employed in the implementation of these studied complexes is clearly defined and described. The paper also presents a comprehensive examination of various modern optimization methods and approaches employed to determine the optimal structure of these complexes. The paper thoroughly discusses the advantages and disadvantages of these methods, while also proposing future development directions that suggest specific adjustments to existing approaches. These adjustments aim to enhance decision-making efficiency and maximize economic benefits. Overall, the paper emphasizes the significance of research in renewable energy sources and hydrogen technologies, underlining their relevance and potential for sustainable energy solutions. In a concise manner, this paper addresses identified problems, highlights research directions, analyzes optimization methods, proposes improvements, and argues for the importance of this research field.